Impoliteness : using language to cause offence - Culpeper, Jonathan, 1966- (Cambridge, UK. : Cambridge University Press, 2011)
'When is language considered'impolite'? Is impolite language only used for anti-social purposes? Can impolite language be creative? What is the difference between'impoliteness' and'rudeness'? Grounded in naturally-occurring language data and drawing on findings from linguistic pragmatics and social psychology, Jonathan Culpeper provides a fascinating account of how impolite behaviour works. He examines not only its forms and functions but also people's understandings of it in both public and private contexts. He reveals, for example, the emotional consequences of impoliteness, how it shapes and is shaped by contexts, and how it is sometimes institutionalised. This book offers penetrating insights into a hitherto neglected and poorly understood phenomenon. It will be welcomed by students and researchers in linguistics and social psychology in particular'--
Includes bibliographical references (p. 263-287) and index.
Keywords: Politeness (Linguistics); English language -- Honorific; Power (Social sciences); Interpersonal relations